Analysis and design of passive pile in open excavation - Kok, Sien Ti (2010)
In recent years, there are rapid development in the construction of massive superstructures. These buildings are often supported by deep foundations such as piles. When construction space becomes a limitation, deep excavation had to be carried out with the presence of existing piles. These piles will eventually be exposed during excavation works, and are expected to provide significant resistance to soil movements even before the full mobilization of designed lateral load. The prediction of soil movement under this condition is only using simplified approach. This leads to underestimation of cracking moment especially when excavation was carried out in a soft clay layer. Underestimating the bending moment in these piles will results in cracked and broken piles. Advances could be realized in design of economical pilesupported foundations with the behaviour accurately predicted if the lateral resistance could be accurately and easily obtained. This research looks into the literature review on the current research on piles under various horizontal loading and focusing on passive piles. The outline of research work conducted in this study includes developing a simple 1-g laboratory model test,conducting few tests of horizontally loaded pile and analyzing the result with an existing three-dimensional finite element software. A case study of a group pile failure in open excavation was modelled. Lastly, parametric study of single spun piles in open excavation was carried out in order to develop pile design guidelines. PLAXIS 3D FOUNDATION software which offers three-dimensional finite element modeling for rock and soil was utilized to develop an analytical model of single pile in open excavation. This model was verified using 1-g laboratory model test result,published centrifuge data and case study. The model verification results showed that this mathematical model was able to predict the magnitude of horizontal soil movement reliably provided the selection of soil constitutive model parameters were done reasonably. Major highlight of the research is based on the model which was used to model a geometry of an open excavation where the single pile is at the toe of the excavation. The soil stiffness ranges from very soft to medium stiff clay underlain by a hard layer. The effects of few parameters are clearly shown in charts namely the soil stiffness, spun pile diameter, excavation slope and depth function. This research also develops practical and suitable design guidelines that are applicable for design use is developed to predict the response of single pile in soft clay excavation. The result of this research was expected to enhance and to contribute to the current state of knowledge and practice regarding pile groups in soft clay excavation.